Professor Chamberlin and Mr. Smith on Advertising - Silcock, T. H. (Review of Economic Studies, 1947)
Professor Chamberlin and Mr. Smith on Advertising Get access T. H. Silcock T. H. Silcock Singapore Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 15, Issue 1, 1947, Pages 34–39, https://doi.org/10.2307/2295926 Published: 01 April 1947